A diaphragm and its preparation method and application
By using a crosslinked network coating composed of chitosan and sulfonate on the lithium metal battery separator, safety issues caused by lithium dendrites are solved, and electrochemical performance is improved and costs are reduced.
Patent Information
- Application Number
- CN202310557398.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-17
AI Technical Summary
In practical applications, lithium metal batteries are limited by safety problems caused by side reactions during lithium dendrites' growth and circulation. The prior art is difficult to take into account both the improvement of electrochemical performance and the reduction of costs.
The polyethylene diaphragm modified with a crosslinked network coating composed of chitosan and sulfonate is improved through sulfonation treatment and multi-layer coating technology, and the expansion of the lithium metal negative electrode is inhibited.
It significantly improves the electrochemical performance of lithium metal batteries, including first-effect, cyclic specific capacity and retention rate, reduces production costs, and improves battery safety.
Smart Images

Figure CN116505188B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a diaphragm and a preparation method and application thereof. Background Art
[0002] Lithium metal batteries are one of the most promising candidates for the next generation of large-scale energy storage devices and for achieving a 1,000-kilometer range for new energy vehicles due to their high theoretical energy density and processability. However, the practical application of lithium metal anodes is limited by safety issues caused by uncontrollable lithium dendrite growth and side reactions during cycling.
[0003] Methods to improve the growth of lithium dendrites and side reactions during the cycle include improving the electrolyte composition to form a stable SEI film, constructing an artificial SEI layer, optimizing the structure of the lithium metal anode, and constructing a 3D lithium metal anode. These methods can alleviate the disordered growth of lithium dendrites to a certain extent and reduce side reactions during the cycle.
[0004] CN114300807A discloses a method for preparing a lithium battery diaphragm, and the specific preparation steps of the method for preparing a lithium battery diaphragm are as follows: S1: polyethylene material, nano glass powder and solvent are mixed uniformly: polyethylene material, nano glass powder and solvent are weighed as diaphragm raw materials, the polyethylene material, nano glass powder and solvent are heated and mixed uniformly through a stirring mechanism to obtain a mixture; S2: the uniformly mixed raw materials are extruded and formed; S3: the formed sheet is heat-drawn into a film; S4: a porous film is formed.
[0005] CN110197884A discloses a polyethylene microporous membrane for lithium battery separator and a preparation method thereof, comprising the following raw materials in proportion by weight: 25-35 g high-density polyethylene, 100 mL liquid paraffin, 1-2 g antioxidant 1010, and nano-silica particle nucleating agent.
[0006] The nanomaterials and high-concentration lithium salts used in the above scheme are expensive, which is not obvious in the small-batch button battery system in the laboratory stage. When applied to the mass production of actual square and soft-pack products, the production cost will increase exponentially, making it difficult to form a commercial scale. Summary of the invention
[0007] The object of the present invention is to provide a diaphragm and a preparation method and application thereof. In the diaphragm of the present invention, the polyethylene diaphragm modified with a cross-linked network coating composed of chitosan and sulfonate greatly improves the electrochemical performance of lithium metal batteries compared with the unmodified one.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a diaphragm, the method comprising the following steps:
[0010] (1) respectively preparing a chitosan solution and a sulfonate solution, and performing a sulfonation treatment on the diaphragm to obtain a pretreated diaphragm;
[0011] (2) coating the chitosan solution on both sides of the pretreated membrane to obtain a chitosan layer, and coating the sulfonate solution on the surface of the chitosan layer to obtain a sulfonate layer;
[0012] (3) Repeat the coating step (2) n times and then let stand to obtain the diaphragm, wherein n>1.
[0013] The method of the present invention can greatly improve the mechanical strength of the diaphragm, alleviate the expansion of the lithium metal negative electrode, improve the thermal stability of the diaphragm, and reduce the safety problems caused by the short circuit of the positive and negative electrode plates due to the thermal shrinkage of the diaphragm. The production process of the materials chitosan and p-hydroxybenzenesulfonic acid used is mature, the cost is low, and it has great economic value.
[0014] Preferably, the chitosan solution in step (1) comprises chitosan and an acidic solution.
[0015] Preferably, the mass fraction a of chitosan in the chitosan solution is 0.01-0.05wt%, for example: 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt% or 0.05wt%.
[0016] Preferably, the solute of the acidic solution includes any one of acetic acid, citric acid, carbonic acid, sulfurous acid or hydrosulfuric acid, or a combination of at least two thereof.
[0017] Preferably, the mass concentration b of the solute in the acidic solution is 0.8-1.5wt%, for example, 0.8wt%, 0.9wt%, 1wt%, 1.2wt% or 1.5wt%.
[0018] Preferably, the solute of the sulfonate solution includes any one of p-hydroxybenzenesulfonic acid, polystyrenesulfonate, 3-(1-vinyl-3-imidazole)propanesulfonate or 3-(1-methyl-3-imidazole)propanesulfonate, or a combination of at least two thereof.
[0019] Preferably, the mass concentration c of the sulfonate solution is 0.001-0.008 wt%, for example, 0.001 wt%, 0.002 wt%, 0.004 wt%, 0.006 wt% or 0.008 wt%.
[0020] Preferably, 0.008<a / b<0.02.
[0021] Preferably, 0.1<c / a<0.6.
[0022] Preferably, the diaphragm in step (1) comprises a polyethylene diaphragm.
[0023] Preferably, the sulfonation treatment comprises immersing the membrane in a liquid containing SO3 - Free radical sulfonation solution.
[0024] Preferably, the SO3 in the sulfonated solution - The mass concentration of the free radicals is 10-30wt%, for example, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.
[0025] Preferably, the immersion time is 6 to 12 hours, for example, 6 hours, 8 hours, 10 hours, 11 hours or 12 hours.
[0026] Preferably, the coating method in step (2) includes spraying.
[0027] Preferably, the thickness of a single layer of the chitosan layer is 0.01-1 μm, for example, 0.01 μm, 0.03 μm, 0.1 μm, 0.5 μm or 1 μm.
[0028] Preferably, the single layer thickness of the sulfonate layer is 0.01-1 μm, for example, 0.01 μm, 0.03 μm, 0.1 μm, 0.5 μm or 1 μm.
[0029] Preferably, in the diaphragm of step (3), the total thickness of the chitosan layer and the sulfonate layer is 0.1-1 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm or 1 μm.
[0030] Preferably, in the diaphragm of step (3), the total thickness of the chitosan layer is M μm, the total thickness of the sulfonate layer is N μm, and 1≤M / N≤1.5.
[0031] Preferably, the standing time in step (3) is 12 to 18 hours, for example: 12 hours, 14 hours, 15 hours, 16 hours or 18 hours, etc.
[0032] During the static process of the present invention, NH3 + and SO3 - Interaction occurs to form a cross-linked network.
[0033] Preferably, vacuum drying treatment is performed after the standing.
[0034] Preferably, the temperature of the vacuum drying treatment is 65-90°C, for example, 65°C, 70°C, 75°C, 80°C or 90°C.
[0035] Preferably, the vacuum drying treatment time is 6 to 24 hours, for example: 6 hours, 8 hours, 10 hours, 15 hours or 24 hours.
[0036] In a second aspect, the present invention provides a membrane, which is prepared by the method described in the first aspect.
[0037] The diaphragm of the present invention comprises a cross-linked network composed of chitosan and sulfonate, wherein the sulfonic acid group increases the migration number of lithium ions, while the chitosan enhances the stability of the structure, improves the mechanical strength of the diaphragm, inhibits the volume expansion of the lithium metal negative electrode during the cycle, prevents its puncture, and thus greatly improves the cycle life.
[0038] In a third aspect, the present invention provides a battery, wherein the battery comprises the separator as described in the second aspect.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The method of the present invention can greatly improve the mechanical strength of the diaphragm, alleviate the expansion of the lithium metal negative electrode, improve the thermal stability of the diaphragm, and reduce the safety problems caused by the short circuit of the positive and negative electrode plates due to the thermal shrinkage of the diaphragm. The production process of the materials chitosan and p-hydroxybenzenesulfonic acid used is mature, low-cost, and has great economic value.
[0041] (2) In the diaphragm described in the present invention, the cross-linked network composed of chitosan and sulfonate, in which the sulfonic acid group increases the migration number of lithium ions, and at the same time, chitosan enhances the stability of the structure, improves the mechanical strength of the diaphragm, inhibits its volume expansion during the cycle of the lithium metal negative electrode, prevents its puncture, and thus greatly improves the cycle life.
[0042] (3) The first efficiency of the battery made of the diaphragm of the present invention can reach more than 99.73%, the specific capacity after one cycle can reach more than 124.5 mAh / g, the specific capacity after 100 cycles can reach more than 123.8 mAh / g, and the specific capacity retention rate after 500 cycles can reach more than 92.7%. The polyethylene diaphragm modified with a cross-linked network coating composed of chitosan and sulfonate greatly improves the electrochemical performance of lithium metal batteries compared to the unmodified one. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram of the structure of the surface of the diaphragm described in Example 1.
[0044] Figure 2 It is a schematic diagram of the structure of the membrane surface after sulfonation treatment described in Example 1. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0046] Example 1
[0047] This embodiment provides a diaphragm, the structural schematic diagram of the diaphragm surface is as follows Figure 1 As shown, the preparation method of the diaphragm is as follows:
[0048] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a polystyrene sulfonate aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% SO3 - The free radical solution was sulfonated for 8 hours and washed three times with deionized water to remove the surface residue. The schematic diagram of the membrane surface structure after sulfonation is shown in Figure 2 As shown;
[0049] (2) spraying the chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.05 μm, and spraying polystyrene sulfonate on the chitosan layer, the thickness of the spraying of polystyrene sulfonate is 0.05 μm;
[0050] (3) Wash the diaphragm obtained in step (2) with deionized water, repeat step (2) and spray four layers of chitosan and four layers of polystyrene sulfonate, the total thickness of the two layers is 0.8 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0051] Example 2
[0052] This embodiment provides a diaphragm, and the preparation method of the diaphragm is as follows:
[0053] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a p-hydroxybenzenesulfonic acid aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% mass concentration SO3 - The free radical solution was sulfonated for 8 h and washed three times with deionized water to remove surface residues;
[0054] (2) spraying a chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.05 μm, and spraying p-hydroxybenzenesulfonic acid on the chitosan layer, the thickness of the spraying p-hydroxybenzenesulfonic acid is 0.05 μm;
[0055] (3) Wash the diaphragm obtained in step (2) with deionized water, repeat step (2) and spray four layers of chitosan and four layers of p-hydroxybenzenesulfonic acid, the total thickness of the two layers is 0.8 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0056] Example 3
[0057] This embodiment provides a diaphragm, and the preparation method of the diaphragm is as follows:
[0058] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a p-hydroxybenzenesulfonic acid aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% mass concentration SO3 - The free radical solution was sulfonated for 8 h and washed three times with deionized water to remove surface residues;
[0059] (2) spraying a chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.02 μm, and spraying p-hydroxybenzenesulfonic acid on the chitosan layer, the thickness of the spraying p-hydroxybenzenesulfonic acid is 0.02 μm;
[0060] (3) Wash the membrane obtained in step (2) with deionized water, repeat step (2) and spray four layers of chitosan and four layers of p-hydroxybenzenesulfonic acid, the total thickness of the two layers is 0.32 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0061] Example 4
[0062] This embodiment provides a diaphragm, and the preparation method of the diaphragm is as follows:
[0063] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a p-hydroxybenzenesulfonic acid aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% mass concentration SO3 - The free radical solution was sulfonated for 8 h and washed three times with deionized water to remove surface residues;
[0064] (2) spraying a chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.05 μm, and spraying p-hydroxybenzenesulfonic acid on the chitosan layer, the thickness of the spraying p-hydroxybenzenesulfonic acid is 0.05 μm;
[0065] (3) Wash the diaphragm obtained in step (2) with deionized water, repeat step (2) and spray two layers of chitosan and two layers of p-hydroxybenzenesulfonic acid, the total thickness of the two layers is 0.4 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0066] Example 5
[0067] This embodiment provides a diaphragm, and the preparation method of the diaphragm is as follows:
[0068] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a polystyrene sulfonate aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% mass concentration SO3 - The free radical solution was sulfonated for 8 h and washed three times with deionized water to remove surface residues;
[0069] (2) spraying the chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.03 μm, and spraying polystyrene sulfonate on the chitosan layer, the thickness of the spraying of polystyrene sulfonate is 0.02 μm;
[0070] (3) Wash the membrane obtained in step (2) with deionized water, repeat step (2) and spray four layers of chitosan and four layers of polystyrene sulfonate, the total thickness of the two layers is 0.4 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0071] Example 6
[0072] This embodiment provides a diaphragm, and the preparation method of the diaphragm is as follows:
[0073] (1) Chitosan was added to an acetic acid aqueous solution with a mass concentration of 1 wt% b to form a chitosan aqueous solution with a mass concentration of 0.01 wt%, and a polystyrene sulfonate aqueous solution with a mass concentration of 0.002 wt% c was prepared. The mixture was stirred continuously until the solute was completely dissolved. The polyethylene membrane was immersed in a 20 wt% mass concentration SO3 - The free radical solution was sulfonated for 8 h and washed three times with deionized water to remove surface residues;
[0074] (2) spraying the chitosan aqueous solution on both sides of the treated polyethylene diaphragm by a spraying process, the thickness of the spraying on both sides is 0.02 μm, and spraying polystyrene sulfonate on the chitosan layer, the thickness of the spraying of polystyrene sulfonate is 0.03 μm;
[0075] (3) Wash the membrane obtained in step (2) with deionized water, repeat step (2) and spray four layers of chitosan and four layers of polystyrene sulfonate, the total thickness of the two layers is 0.4 μm, M / N=1, and stand for 12 hours. Under the action of static electricity, NH3 + and SO3 - The membrane was dried at 90° C. in vacuum for 10 h to obtain the membrane.
[0076] Example 7
[0077] The difference between this embodiment and embodiment 1 is that the mass fraction a of chitosan in the chitosan solution is 0.005 wt %, and a / b=0.005. Other conditions and parameters are exactly the same as those in embodiment 1.
[0078] Example 8
[0079] The difference between this embodiment and embodiment 1 is that the mass fraction a of chitosan in the chitosan solution is 0.025 wt %, and a / b=0.025. Other conditions and parameters are exactly the same as those in embodiment 1.
[0080] Example 9
[0081] The only difference between this embodiment and embodiment 1 is that the mass fraction c of the polystyrene sulfonate in the polystyrene sulfonate aqueous solution is 0.0008 wt %, and c / a=0.08. Other conditions and parameters are exactly the same as those in embodiment 1.
[0082] Example 10
[0083] The only difference between this embodiment and embodiment 1 is that the mass fraction c of polystyrene sulfonate in the polystyrene sulfonate aqueous solution is 0.008 wt %, and c / a=0.8. Other conditions and parameters are exactly the same as those in embodiment 1.
[0084] Embodiment 11
[0085] The difference between this embodiment and embodiment 1 is that the thickness of the chitosan layer is set to 0.04 μm, M / N=0.8, and other conditions and parameters are exactly the same as those in embodiment 1.
[0086] Example 12
[0087] The difference between this embodiment and embodiment 1 is that the thickness of the chitosan layer is set to 0.08 μm, M / N=1.6, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0088] Comparative Example 1
[0089] This comparative example directly uses a polyethylene diaphragm.
[0090] Comparative Example 2
[0091] The only difference between this comparative example and Example 1 is that the diaphragm is not subjected to sulfonation treatment, and the other conditions and parameters are exactly the same as those in Example 1.
[0092] Comparative Example 3
[0093] The only difference between this comparative example and Example 1 is that the chitosan layer is not sprayed, and the other conditions and parameters are exactly the same as those in Example 1.
[0094] Comparative Example 4
[0095] The only difference between this comparative example and Example 1 is that the sulfonate layer is not sprayed, and the other conditions and parameters are exactly the same as those in Example 1.
[0096] Comparative Example 5
[0097] The only difference between this comparative example and Example 1 is that sulfonate and chitosan are mixed and coated, and other conditions and parameters are exactly the same as those in Example 1.
[0098] Performance Testing:
[0099] With lithium metal as the negative electrode, lithium iron phosphate as the positive electrode, 1.0M LiPF6 in EC:DEC:EMC=1:1:1Vol% as the electrolyte, the separators prepared in the embodiment and the comparative example were assembled into button-type half-cells, and the electrochemical performance was tested. The test conditions are as follows: the charge cut-off voltage is 4V, the discharge cut-off voltage is 1.5V, the charge and discharge current is 0.1C, the cycle current is 2C, the nominal gram capacity is 175mAh / g, and the test results are shown in Table 1:
[0100] Table 1
[0101]
[0102] As can be seen from Table 1, from Examples 1-6, the first efficiency of the battery made with the diaphragm of the present invention can reach more than 99.73%, the specific capacity after one cycle can reach more than 124.5 mAh / g, the specific capacity after 100 cycles can reach more than 123.8 mAh / g, and the specific capacity retention rate after 500 cycles can reach more than 92.7%. The polyethylene diaphragm modified with a cross-linked network coating composed of chitosan and sulfonate greatly improves the electrochemical performance of lithium metal batteries compared to the unmodified one.
[0103] By comparing Example 1 with Examples 7-8, it can be seen that in the preparation process of the diaphragm described in the present invention, the ratio a / b of the mass fraction a of chitosan in the chitosan solution used to the mass concentration b of the solute in the acidic solution will affect the effect of the prepared diaphragm. When a / b is controlled at 0.008-0.02, the performance of the prepared diaphragm is better. If a / b is too large, the dispersibility of chitosan is poor and the pores of the diaphragm are uneven. If a / b is too small, the process cannot occur.
[0104] By comparing Example 1 with Examples 9-10, it can be seen that in the preparation process of the diaphragm described in the present invention, the ratio c / a of the mass concentration c of the sulfonate solution used to the mass fraction a of chitosan in the chitosan solution will affect the effect of the prepared diaphragm. When c / a is controlled at 0.1-0.6, the performance of the prepared diaphragm is better. If c / a is too large, too much sulfonate is easily dispersed in the pores and affects the transmission of lithium ions. If c / a is too small, the sulfonate layer cannot be fully combined with chitosan and the ideal effect cannot be achieved.
[0105] By comparing Example 1 and Examples 11-12, it can be seen that in the diaphragm described in the present invention, the ratio M / N of the total thickness M of the chitosan layer to the total thickness N of the sulfonate layer will affect the effect of the prepared diaphragm. When M / N is controlled at 1 to 1.5, the performance of the prepared diaphragm is better. If M / N is too large, the lithium ion diffusion distance of the entire diaphragm is large, which hinders the lithium ion transmission. If M / N is too small, the mechanical strength is too low and it cannot play a buffering role in suppressing expansion during the cycle.
[0106] From the comparison between Example 1 and Comparative Example 1, it can be seen that in the diaphragm of the present invention, the polyethylene diaphragm modified with the cross-linked network coating composed of chitosan and sulfonate greatly improves the electrochemical performance of the lithium metal battery compared with the unmodified one.
[0107] From the comparison between Example 1 and Comparative Example 2, it can be seen that the sulfonic acid group improves the deposition and stripping ability of lithium ions, so that the surface of the diaphragm has a large number of sulfonic acid groups, which is more conducive to the uniform deposition of lithium ions. Therefore, the polyethylene diaphragm treated with sulfonic acid groups improves the initial efficiency of the lithium metal battery compared to the unmodified one.
[0108] From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that a single chitosan or sulfonate coating has little effect on the volume expansion and kinetics of the lithium metal negative electrode during the cycle.
[0109] By comparing Example 1 and Comparative Example 5, it can be seen that the chitosan composite coating greatly increases the toughness of the diaphragm through the sandwich structure, inhibits the volume expansion during the circulation of metallic lithium, and the polar groups exposed in the sandwich structure of chitosan and sulfonate greatly enhance the lithium ion transmission capacity and improve the long-term cycle performance of lithium metal batteries.
[0110] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a diaphragm, characterized in that: The preparation method comprises the following steps: (1) preparing a chitosan solution and a sulfonate solution respectively, and performing a sulfonation treatment on the diaphragm to obtain a pretreated diaphragm; The sulfonation treatment includes immersing the membrane in a solution containing SO3 - In the sulfonated solution of free radicals; (2) coating the pretreated membrane with a chitosan solution to obtain a chitosan layer, and coating the surface of the chitosan layer with a sulfonate solution to obtain a sulfonate layer; (3) repeating the coating step (2) for n times and then allowing the membrane to stand to obtain the membrane, wherein n>1; The monolayer thickness of the chitosan layer is 0.01-1 μm; the monolayer thickness of the sulfonate layer is 0.01-1 μm; The total thickness of the chitosan layer and the sulfonate layer is 0.1-1 μm; The total thickness of the chitosan layer is M μm, the total thickness of the sulfonate layer is N μm, and 1≤M / N≤1.
5.
2. The preparation method according to claim 1, characterized in that The chitosan solution in step (1) comprises chitosan and an acidic solution.
3. The preparation method according to claim 2, characterized in that: The mass fraction a of chitosan in the chitosan solution of step (1) is 0.01-0.05wt%.
4. The preparation method according to claim 2, characterized in that: The solute of the acidic solution in step (1) includes any one of acetic acid, citric acid, carbonic acid, sulfurous acid or hydrosulfuric acid, or a combination of at least two thereof.
5. The preparation method according to claim 3, characterized in that: The mass concentration b of the solute in the acidic solution of step (1) is 0.8~1.5wt%.
6. The preparation method according to claim 1, characterized in that: The solute of the sulfonate solution in step (1) includes any one of p-hydroxybenzenesulfonic acid, polystyrenesulfonate, 3-(1-vinyl-3-imidazole)propanesulfonate or 3-(1-methyl-3-imidazole)propanesulfonate, or a combination of at least two thereof.
7. The preparation method according to claim 3, characterized in that: The mass concentration c of the sulfonate solution in step (1) is 0.001-0.008 wt%.
8. The preparation method according to claim 5, characterized in that: 0.008<a / b<0.
02.
9. The preparation method according to claim 7, characterized in that: 0.1<c / a<0.
6.
10. The preparation method according to claim 1, characterized in that: The diaphragm in step (1) comprises a polyethylene diaphragm.
11. The preparation method according to claim 1, characterized in that: SO3 in the sulfonation solution of step (1) - The mass concentration of free radicals is 10~30wt%.
12. The preparation method according to claim 1, characterized in that: The immersion time in step (1) is 6 to 12 hours.
13. The preparation method according to claim 1, characterized in that: The coating method in step (2) includes spraying.
14. The preparation method according to claim 1, characterized in that: The standing time in step (3) is 12 to 18 hours.
15. The preparation method according to claim 1, characterized in that: The step (3) is followed by vacuum drying after standing.
16. The preparation method according to claim 15, characterized in that: The temperature of the vacuum drying treatment is 65-90°C.
17. The preparation method according to claim 15, characterized in that The vacuum drying process lasts for 6 to 24 hours.
18. A diaphragm, characterized in that: The diaphragm is prepared by the method according to any one of claims 1 to 17.
19. A battery, characterized in that: The battery comprises the separator according to claim 18.
Citation Information
Patent Citations
Polyethylene microporous membrane for lithium battery diaphragm and preparation method thereof
CN110197884A
Preparation method of electrolyte membrane and solid-state lithium battery
CN106654367A
Modified separator, preparation method thereof and lithium ion battery
CN109560238A